Effect of combined drought and high temperature stress onwheat (Triticum aestivum): Insights into grain yield and quality dynamics - MEENA, SHASHI; TARIA, SUKUMAR; YADAV, SHEEL; S, KOUSALYA; KUMAR, SUDHIR; CHINNUSAMY, VISWANATHAN; ARORA, AJAY (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during winter (rabi) season of 2020–21 and 2021–22 at ICAR-Indian Agricultural Research Institute, New Delhi to assess the individual and combined effects of drought and heat stresses on bread wheat (Triticum aestivum L.), focusing on yield, yield-contributing parameters, and grain nutritional quality in four contrasting wheat genotypes (C306, HD2967, Raj3765 and WL711). The experiment was laid out in completely randomized design (CRD) with 15 replications of each genotype. The results revealed that combined drought and heat stress had a more severe impact on yield-related traits compared to individual stresses. Yield losses under drought stress ranged from 17.7–32.24%, while heat stress alone caused reductions of 29.98–46.55%. However, the combined stress led to the highest yield loss (42.13–61.06%), emphasizing the additive detrimental effects of both stresses. Similarly, 1000-kernel weight (TKW) declined significantly under combined stress conditions, with reductions ranging from 33.22–52.23%, due to impaired starch synthesis and reduced enzymatic activity. Genotype Raj3765 exhibited the highest tolerance, followed by C306, HD2967, and WL711, as indicated by the Stress Susceptibility Index (SSI) and Yield Stability Ratio (YSR). Additionally, nutritional quality assessments showed a decline in zinc (Zn) and iron (Fe) concentrations under drought and combined stresses, with Raj3765 exhibiting the least reduction and WL711 the highest. Despite reductions in starch content, protein content increased under heat stress, suggesting differential regulation of nitrogen metabolism. These findings highlight the necessity of breeding wheat varieties with enhanced resilience to multiple stress factors to sustain grain yield and nutritional quality under climate change scenarios.